Muralist artivism and sense of belonging in public spaces - Rodríguez Valverde, Gilda Dalila (2025)
This article explores muralist artivism as a strategy to strengthen the sense of belonging in public spaces, especially in cities like Lima, which are affected by urban fragmentation and loss of identity. The study seeks to understand how muralism contributes to the construction of identity in Lima's public spaces. The qualitative methodology included documentary review, photographic analysis, and ethnographic observation. The research focused on conceptualizing public space from architectural, anthropological, The results show that community murals in Lima not only beautify but also act as agents of social transformation. They generate changes in the perception of inhabitants, strengthening their sense of belonging and promoting community values. Community participation in the creation of murals is key to citizen empowerment and the strengthening of social networks. Furthermore, the murals have improved the perception of safety and well-being in the neighborhoods, transforming deteriorated spaces into places for gathering and expression. The symbolic elements in these works serve as visual communication tools that transmit community values and create an emotional connection with the environment. In conclusion, muralist artivism is a powerful tool that reinforces a sense of belonging and neighborhood identity, transforms spaces, promotes citizen participation, and communicates cultural and social values.sociological, and artistic perspectives. The analysis of the murals was structured in tables, considering pre-iconographic, iconographic, and iconological levels, along with contextual data and connotative interpretations.